Perception of social and emotional characteristics through smile (Research, Society and Development, 2022)
Introduction: The concept of beauty, however a subjective issue, is overvalued in some societies, especially in Brazil. Beautiful people enjoy social advantages and are best evaluated for having positive characteristics. Objective: To quantify, by means of a questionnaire, the ability of interviewees, to evaluate / intuit / attribute specific characteristics to unknown people, starting from an observational point of view by means of different photos. Methods: Six different photos were designed for undergraduate students, each representing a smile with different aesthetic changes. Participants answered a questionnaire that contained 10 statements regarding emotional and social characteristics and, afterwards, scoring whether or not they agreed with each statement for each evaluated image. Results: A better evaluation was obtained of image considered having harmonic smile, while greater negative characteristics were attributed to smiles with aesthetic changes, such as fractures, diastema, unsatisfactory restorations, and color changes. Conclusion: According to this study, it can be concluded that dental aesthetics influence the evaluation and judgment of certain characteristics influencing on the emotional and social background.  It is the duty of the dental surgeon to be attentive to this subjective step when facing unaestethic smiles, allowing a greater understanding the psycho-social context of the patient.